Report of a Complicated Case of Couvelaire Uterus - Hamideh Parsapour; Neda Shafie; Amir Mohammad Salehi; Zeinab Assareh (Case Reports in Medicine)
Couvelaire uterus (CU) is a rare complication in the life-threatening placental abruption (PA) that consists of a state of blood infiltration of the uterine myometrium and serosa. The incidence is around 1% and the treatment of choice is obstetric hysterectomy, however, in some cases, close monitoring and timely decision-making can prevent hysterectomy. Herein, we present a rare and serious case of CU with uterus preservation in a young multiparous with a high-risk pregnancy.